Mentally representations about cancer and its etiology of parents of children diagnosed with cancer - Ruda Santolaria, María Lourdes (2001)
The following is an exploratory study that intends to precise the way in which a group of parents of children diagnosed with cancer mentally represent this disea~e and its etiology. For this, 63 parent of 50 children who were beginning their treatment were interviewed. At a qualitative leve!, a content analysis wa~ carried out which allowed the definition of representational categories. With the frequency registration of the latest, a statistical analysis of the main component was carried out which informed of the presence of twelve representational groups. The results show us that although explicitly there predominates the representation of cancer as a curable disease if it is diagnosed soon enough and it receives treatment, deep down persists the link of oncological processes with death. The differences found in the representations of fathers and mothers of a specific child about this disease also reveal the importance of the personal element in the formation of them. The social-economical and cultural variables and, the presence of family antecedent of malignan! neoplasm, are the ones which mark the greater differences in the intensity with which these representational groups appear.